Are taxes or user-fees more popular among politicians? The case of childcare - Friedrich Breyer; Maj-Britt Sterba (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
How shall publicly provided excludable goods be financed - by general taxation or user fees? Prominent applications are in education, notably universities and early childcare. The general conclusion of the existing literature is that exclusive tax financing is neither efficient nor desirable under widely shared distributive goals. A striking example is childcare because here fees are often made dependent on parents' income. Given the rather clear arguments in favor of user fees for formal childcare, it is surprising to notice that some German states with leftist governments have abolished user fees and replaced them with pure tax financing. It is the purpose of this research to investigate the attitudes of politicians towards user fees for publicly funded childcare and to explore the justifications given for these attitudes. This was done within face-to-face online interviews with an embedded survey with members of eight federal state legislatures. The survey results confirm the experience of real political decisions in that left-leaning politicians tend to oppose parental fees. They do so mainly with the justification that "education must be free for all". Right-leaning politicians tend to support fees and consider an abolition as helping mainly the rich and a problem for the quality of childcare. We discuss how these results can be reconciled with the redistributive goals of leftist parties.
urn:nbn:de:bsz:352-2-1i4dlep8bcuga9
Keywords: 320; Childcare fees; legislators; Germany; survey